Applying livelihood approaches to natural resource management initiatives: - Ashley, Caroline (Overseas Development Institute, 2000)
This paper reviews different uses of livelihoods analysis in four project /programmes, and identifies lessons learnt on the application approach. All four examplé explored how rural livelihoods affect and are affected by natural resource management initiatives.